Heterogeneity of Intermediate Care Organization Within a Single Healthcare System - Aaron S. Case, MD, MHS; Chad H. Hochberg, MD, MHS; Binu Koirala, PhD, MGS, BSN, RN; Eleni Flanagan, DNP, MBA; Souvik Chatterjee, MD; William N. Checkley, MD, PhD; Ayse P. Gurses, PhD, MS, MPH; David N. Hager, MD, PhD (Critical Care Explorations)
Intermediate care (IC) is prevalent nationwide, but little is known about how to best organize this level of care. Using a 99-item cross-sectional survey assessing four domains (hospital and physical IC features, provider and nurse staffing, monitoring, and interventions/services), we describe the organizational heterogeneity of IC within a five-hospital healthcare system. Surveys were completed by nurse managers from 12 (86%) of 14 IC settings. Six IC settings (50%) were embedded within acute care wards, four (33%) were stand-alone units, and two (17%) were embedded within an ICU. All had a nurse-to-patient ratio of 1:3, provided continuous cardiac telemetry, continuous pulse oximetry, high-flow nasal oxygen, and bedside intermittent hemodialysis. Most (> 50%) permitted arterial lines, frequent nursing assessments (every 2 hr), and noninvasive ventilation or mechanical ventilation via a tracheostomy. Vasopressors were less often permitted (< 25% of settings). Models of IC vary greatly within a single healthcare system.